THE ROLE OF TRAVEL VLOGGERS IN INCREASING THE POPULARITY OF CREATIVE TOURISM DESTINATIONS: A PHENOMENOLOGICAL STUDY - Musafa, Musafa (PT. Altin Riset Publishing, 2024)
Travel Vloggers, as professionals in the tourism industry, utilize social media to share their experiences in various tourist destinations. Their content aims to promote the beauty of tourist attractions and educate the audience about the experience. However, building a strong presence on social media is not easy. Travel Vloggers need recognition from the audience to achieve their goals. This research uses a qualitative phenomenological approach to examine how Travel Vloggers build their existence on social media and how they contribute to increasing the popularity of creative tourism destinations. The results show that there are similarities between Travel Vlogger content and blog maker content. In addition, national awards are a form of recognition for Travel Vloggers as their professional identity.